INTEGRASI NILAI-NILAI ISLAM TERHADAP BIMBINGAN DAN KONSELING DI SEKOLAH - Jasmine, Putri; Johan, Budi; Rahmadina, Oktavia; Putriviandi, Naila Najah; Jauza, Nathania Tsany; Kautsar, Syifa (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Guidance and Counseling (BK) in schools plays a crucial role in helping students overcome problems, develop their potential, and achieve a balanced and meaningful life. Integrating Islamic values in BK practices provides a holistic approach relevant to Islamic teachings, such as understanding the Qur'an and Hadith, Islamic-based professional ethics, holistic approaches, counseling based on Islamic morals, and using examples from the lives of the Prophet and his companions. These values include Muamalah, Akhlakul Karimah, and Amaliah, which play roles in shaping students' character. The implementation of Islamic values in BK results in wise, friendly, perfectionist, humble, and religious behavior. Counselors are required to possess competencies including pedagogic, personality, social, and professional competencies that reflect the knowledge, skills, and behaviors established in BK services